Chapter I laudari gesuati: la raccolta poetica del Bianco da Siena - serventi, silvia (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The extensive poetic collection of Bianco da Siena reflects the rich spirituality of Jesuates as, under the generic definition of «lauds», there are writings belonging to different literary genres, such as the abecedary, the acrostic, the epistle and the preaching in verse, the mystical, penitential, santoral, Marian lauda, ​​in addition to the paraphrase of prayers. The characteristic themes of «jesuate piety» often emerge in his compositions, such as the repetition of the name of Jesus, the desire to be dishonored, the importance of prayer, the Immaculate Conception, the devotion to the pope and to the clergy. A «jesuate specificity» emerges, intended to spread the «affective mysticism» of Carthusian matrix first of all among the Jesuates, but more generally among the true lovers of God.